1993
DOI: 10.1021/jf00030a030
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization of atrazine ozonation products. Application to the development of a pesticide waste disposal system

Abstract: Development of remediation techniques for unusable pesticide wastes has led to a binary scheme involving ozonation followed by biomineralization of the resultant oxidized pesticides. Preliminary field tests of this technique indicated that the s-triazines were somewhat more recalcitrant than the other pesticides present. Further experiments identified the final ozonation products of atrazine, the most widely used s-triazine, as 4-acetamido-6-amino-2-chloro-s-triazine (CDAT) and chlorodiamino-s-triazine (CAAT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…Thus, the mineralization of CAAT requires microorganisms that can effectively utilize CAAT as a nitrogen source even in the presence of inorganic nitrogen sources, such as ammonium nitrate (a typical fertilizer found in pesticide waste). Such an organism was isolated from sewage sludge and identified as a bacterium (K. terragena, strain DRS-I) (Leeson et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the mineralization of CAAT requires microorganisms that can effectively utilize CAAT as a nitrogen source even in the presence of inorganic nitrogen sources, such as ammonium nitrate (a typical fertilizer found in pesticide waste). Such an organism was isolated from sewage sludge and identified as a bacterium (K. terragena, strain DRS-I) (Leeson et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…High ammonia concentrations (ca. 1%) were found a priori to be responsible for the inhibition of microbial degradation (Leeson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…3a). Leeson et al (1993) reported enhanced microbial degradation of various pesticides following chemical pretreatment. They observed complete degradation of atrazine after applying corn syrup to pretreated soil containing a high nitrogen concentration.…”
Section: Secondary Treatment Of Windrowed Soilmentioning
confidence: 99%
“…Degradation can be maximized by combining chemical treatment (e.g., Fe 0 ) with biological degradation. Enhanced microbial degradation of pesticides (Leeson et al 1993), polyaromatic hydrocarbons (PAHs; Nam et al 2001), and explosives (Adam et al 2005) has been reported following chemical pretreatment of soil and water.…”
mentioning
confidence: 99%
See 1 more Smart Citation